1988
DOI: 10.1021/bi00418a065
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic specificity of cholinergic ligands: .alpha.-conotoxin SI

Abstract: The alpha-conotoxins are small peptide neurotoxins from the venom of fish-hunting cone snails which block nicotinic acetylcholine receptors (nAChRs). We describe the purification, characterization, and chemical synthesis of a new alpha-conotoxin from Conus striatus, alpha-conotoxin SI. In contrast to other AChR ligands, alpha-SI discriminates between different vertebrate nAChRs. The sequence of alpha-conotoxin SI is Ile-Cys-Cys-Asn-Pro5-Ala-Cys-Gly-Pro-Lys10-Tyr-Ser-Cys-NH2. This sequence was confirmed by chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
76
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(80 citation statements)
references
References 15 publications
(15 reference statements)
3
76
0
Order By: Relevance
“…These IV samples contained peptides that were previously characterized from the DV of this species, including the calcium-channel blocker ω-SVIA (Ramilo et al, 1992) and nicotinic acetylcholinereceptor blockers α-SI and α-SII (Ramilo et al, 1992;Zafaralla et al, 1988), as confirmed by MALDI-MS. Interestingly, neither s4a nor s4b were observed components of the IV from these snails.…”
Section: Variation In the Composition Of Injected Venom Inmentioning
confidence: 96%
See 2 more Smart Citations
“…These IV samples contained peptides that were previously characterized from the DV of this species, including the calcium-channel blocker ω-SVIA (Ramilo et al, 1992) and nicotinic acetylcholinereceptor blockers α-SI and α-SII (Ramilo et al, 1992;Zafaralla et al, 1988), as confirmed by MALDI-MS. Interestingly, neither s4a nor s4b were observed components of the IV from these snails.…”
Section: Variation In the Composition Of Injected Venom Inmentioning
confidence: 96%
“…It is apparent both by the number of peaks that appear in the chromatograms, and the masses labeled, that IV is by no means identical to DV and contains a small subset of DV peptides, primarily less hydrophobic ones. Identifiable DV and IV peptides were fully processed from their propeptides and contained the known post-translational modifications such as carboxy-terminal amidation (s4a, ω-SVIB and α-SI) and proline hydroxylation (s4a and ω-SVIA; Craig et al, 1998;Ramilo et al, 1992;Zafaralla et al, 1988). Peptides s4a and s4b were also modified by O-glycosylation and pyroglutamylation (Craig et al, 1998).…”
Section: Comparison Of Duct Venom and Injected Venom Samples Inmentioning
confidence: 99%
See 1 more Smart Citation
“…A well defined subgroup of ␣-conotoxins, referred to as the ␣3/5 2 subfamily conotoxins (Table I), are antagonists of neuromuscular receptors and show, except for ␣-conotoxin SI (9,10), binding preference to the ␣ 1 /␥ subunit interface of Torpedo nAChR. On the other hand, more recently found ␣A-conotoxins differ from the ␣3/5 subfamily conotoxins in the amino acid sequences (11,12) as well as in their threedimensional structures (13).…”
mentioning
confidence: 99%
“…1 The majority of ␣-conotoxins isolated from fishhunting cone snails, including GI, GIA, and GII from Conus geographus (4), MI from Conus magus (5), and SI and SII from Conus striatus (6,7), show extensive structural homology, a conserved cysteine framework, and target the muscle subtype of the nAChR. The ␣-conotoxins PnIA and PnIB from a molluschunting cone snail, Conus pennaceus (8), and ImI from a wormhunting cone snail, Conus imperialis (9) share a similar cysteine framework to ␣-conotoxins from fish-hunting cones, but have a different sequence pattern and target the neuronal subtypes of the nAChR.…”
mentioning
confidence: 99%